2017
DOI: 10.1080/10942912.2017.1289959
|View full text |Cite
|
Sign up to set email alerts
|

Milk-clotting properties of plant rennets and their enzymatic, rheological, and sensory role in cheese making: A review

Abstract: Plant rennets hold an important position among various coagulants used in cheese technology. The selection of a suitable plant coagulant is important due to the increasing global demands of cheese alongside reduced supply of calf rennet. Thus, a literature synthesis is presented to investigate recent achievements on their functional properties and enzymatic role in cheese making. Efforts have also been done to compare certain rheological and sensory properties of final products, arising from some plant-and ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 91 publications
1
73
1
Order By: Relevance
“…The type of protease (e.g., cysteine, serine and aspartic) and its specificity is of great relevance and defines its use in food processing. For cheesemaking, in general, a protease with a higher ratio between specific activity for milk coagulation (milk clotting activity, MCA) and enzymatic non-specific proteolytic activity (PA) (MCA/PA ratio) is more capable to form curd, obtaining higher yield and less bitterness development during cheese processing, while a low ratio may result in lower curd recovery, weak curd firmness and the release of bitter peptides that affect the sensory properties of the final product (Amira, Besbes, Hamadi, & Blecker, 2017;Mazorra-Manzano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of protease (e.g., cysteine, serine and aspartic) and its specificity is of great relevance and defines its use in food processing. For cheesemaking, in general, a protease with a higher ratio between specific activity for milk coagulation (milk clotting activity, MCA) and enzymatic non-specific proteolytic activity (PA) (MCA/PA ratio) is more capable to form curd, obtaining higher yield and less bitterness development during cheese processing, while a low ratio may result in lower curd recovery, weak curd firmness and the release of bitter peptides that affect the sensory properties of the final product (Amira, Besbes, Hamadi, & Blecker, 2017;Mazorra-Manzano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, sheep cheese produced with this type of coagulant has become highly valued because of its special taste and organoleptic properties (Fern andez et al, 2006;Roseiro et al, 2003). These vegetable coagulants have other interesting uses concerning specific targets, for example, cheese production with these natural enzymes can be aimed at lactovegetarian consumers and ecological markets (Gal an, Cabezas, & Fern andez-Salguero, 2012; Khaldi, Sonnante, & El Gazzah, 2012) or to overcome religious restrictions (Amira et al, 2017;Roseiro et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Panelists chose formula II as the best color, since it has a yellowish-white color. According to Ben-Amira et al (2017), cheese made from cow's milk without coloring will produce cheese that is yellowishwhite. Yellow comes from fat-soluble carotene pigments.…”
Section: Formula Optimization and Verification Of The Optimum Formulamentioning
confidence: 99%
“…The effect of the lime extract is not only sour taste, but it also causes a slightly bitter taste. According to Ben-Amira et al (2017), the bitter taste in oranges is influenced by the presence of two compounds, namely flavonoids and limonoids. The main component of flavonoids is naringin, which gives the impression of an astringent to bitter taste.…”
Section: Fullmentioning
confidence: 99%
“…The use of cardoon flowers as coagulant allows for the production of high‐quality cheeses with specific characteristics and it has been demonstrated that additional cleavage of milk caseins contributes to the final texture and flavor properties of these cheeses . For cheese making, in general, the effects on the yield, texture and bitterness are due to the ratio between specific milk clotting activity and enzymatic non‐specific proteolytic activity . Guiné et al .…”
Section: Bioactive Compoundsmentioning
confidence: 99%